Effect similarities strategy in classification skill development in science on basic fourth grade (semi-empirical study in lattakia city) - Sultan, Manal; Hameed, Diana (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
This research aims to explore impact of using similarities strategy in classification skill development in science on Fourth Grade students in lattakia city, to achieve the research target, target group was taken from Fourth Grade students so: )29( students for experimental group and )35( students for control group. and the searcher designed an educational program based on similarities strategy applied on the experimental group, she also designed a performance test and a note card of classification skill. And she used semi-empirical method. the research reached the following results : -There are statistically significant differences between the averages scores of the experimental and control groups in the direct post application on each of skill note card and the test of classification skill performance in favor of the experimental group’s degrees. -There are no differences between the averages scores of students of the experimental group in direct post applying on each of skill note card and the test of classification skill performance according to sexual variable. -There are no statistically significant differences between the averages scores’s students of the experimental group in direct and deferred post application in favor of the post application on each of skill note card and the test of classification skill performance. According to the research results, the searcher reaches to, the necessity of doing continuous training courses for the teachers to give them sight into recent methods in general and specially in biology teaching, and steering teacher,s attention towards classification skill .